Differential effects of leucine supplementation in young and aged mice at the onset of skeletal muscle regeneration. (July 2016) - Perry, Richard A.; Brown, Lemuel A.; Lee, David E.; Brown, Jacob L.; Baum, Jamie I.; Greene, Nicholas P.; Washington, Tyrone A.
Highlights: In young mice, leucine had a no effect on markers of protein synthesis post-injury. In aged mice, leucine had an effect on markers of protein synthesis post-injury. In young mice, leucine acts independently of mTOR post-injury. In aged mice, leucine acts in an mTOR-dependent manner to increase protein synthesis. Abstract: Aging decreases the ability of skeletal muscle to respond to injury. Leucine has been demonstrated to target protein synthetic pathways in skeletal muscle thereby enhancing this response. However, the effect of aging on leucine-induced alterations in protein synthesis at the onset of skeletal muscle regeneration has not been fully elucidated. The purpose of this study was to determine if aging alters skeletal muscle regeneration and leucine-induced alterations in markers of protein synthesis. The tibialis anterior of young (3 months) and aged (24 months) female C57BL/6J mice were injected with either bupivacaine or PBS, and the mice were given ad libitum access to leucine-supplemented or normal drinking water. Protein and gene expression of markers of protein synthesis and degradation, respectively, were analyzed at three days post-injection. Following injury in young mice, leucine supplementation was observed to elevate only p-p70S6K. In aged mice, leucine was shown to elicit higher p-mTOR content with and without injury, and p-4EBP-1 content post-injury. Additionally in aged mice, leucine was shown to elicit higher content of relative p70S6K post-injury. Our study shows that leucine supplementation affects markers of protein synthesis at the onset of skeletal muscle regeneration differentially in young and aged mice.